Educomusicalização: a educação musical sob a perspectiva da educomunicação - Uliana, Silvana (2017)
This research integrates the interrelation of Educommunication and Music teaching, with the objective of investigating the possible contributions of Educommunication actions in the Musical teaching in a Music class at the Public Conservatorium of Music Cora Pavan Capparelli (CEMCPC) in Uberlandia-Minas Gerais. The research was realized in three phases, in the first phase happened the observations of the lessons of a teacher, in a musicalization class with students of musical initiation. The second phase, a teacher training course about the Educommunicative concept and practice and the third phase, over again with the observations of the teaching actions view according to the Educommunicative characteristics. The methodology was based on the qualitative approach in the participant research modality and the procedures of data collection were interviews and observations. The theme "Teaching Music in the Educommunicative perspective" was based on the contributions of the main authors such as Freire (1971, 1987), Kaplún (1984) and Soares (1999, 2000, 2002, 2011, 2014, 2016) with concepts and fundamentals about Educommunication, and with the possible transposition and reflections of its foundations for the music teaching, it was possible to approach them in the synthesis of this research: Educommusicalization. The data analysis was based on some characteristics of Educommunication as the dialogue, participation, interaction, exchange of knowledge, autonomy, protagonism, planning, organization and interdisciplinarity. The results pointed to the presence of the educommunicative characteristics in the teacher's actions evidencing important aspects of this research and opening possibilities for new perspectives to Music teaching.